SOSIALISASI UJI AKTIVITAS ANTIINFLAMASI EKSTRAK ETANOL DAUN KEDONDONG (Spondias dulcis Frost) TERHADAP TIKUS JANTAN YANG DIINDUKSI KARAGENAN - Ahmad Syukur Hasibuan (JURNAL PENGMAS KESTRA (JPK), 2021)
In the treatment of inflammation, there are several chemical drugs, namely steroidal and non-steroidal anti-inflammatory drugs, but because they have many side effects, anti-inflammatory drugs are developed from natural ingredients, especially plants. Plants that are scientifically proven to have anti-inflammatory properties, one of which is kedondong leaves because kedondong leaves contain flavonoid secondary metabolites as anti-inflammatory compounds. The method used in this study was paw edema, namely by induction of carrageenan 0.1 ml as an irritant on the soles of the rat's feet for 360 minutes with the parameter observed was the inhibition of edema in the feet of rats using a plethismometer. This study was an experimental study that was divided into 5 groups, namely the control group. positive (Diclofenac Sodium 9 mg/kgBW), negative control (Na-Cmc 0.55), and three doses tested, namely 100 mg/kgBW, 300 mg/kgBW and 500 mg/kgBW. The results of this study showed a significant difference (P> 0.05) with the conclusion that the three doses tested, namely 100 mg/kgBW, 300 mg/kgBW and 500 mg/kgBW had an anti-inflammatory effect where the more effective dose was 300 mg/kg kgBB.